Parasitic nematodes and their management in major spices - EAPEN, K V RAMANA, SANTHOSH J (Journal of Spices and Aromatic Crops, 1995)
Black pepper (Piper nigrum), cardamom (Elettaria cardamomum), ginger (Zingiber officinale), turmeric (Curcuma longa) and tree spices are the major spices cultivated in India. Several plant parasitic nematodes are reported on these spice crops and among them, root knot nematodes (Meloidogynespp.), burrowing nematodes (Radopholus similis and root lesion nematodes (Pratylenchus spp.) are the major nematode pests of economic importance. Plant parasitic nematodes are primary incitants of slow decline disease of black pepper. Root knot nematodes are a seious constraint to cardamom cultivation, especially in nurseries. In ginger and turmeric, all three of them cause significant damage. However, not much attention has been given to nematodes of tree spices. The major symptoms of nematode attack, the nature and extent of damage, their interaction with other soil borne microorganisms and various control measures are discussed. Considering the export oriented nature of these crops, emphasis has been given on integrated nematode management with minimum use of chemicals.